Fat activism : a radical social movement - Cooper, Charlotte, 1968- (HammerOn Press, 2016)
Charlotte Cooper, a fat activist with more than 30 years experience, lifts the lid on a previously unexplored social movement and offers a fresh perspective on one of the major problems of our times. In her expansive, intelligent grassroots study she: - Reveals details of fat activist methods and approaches - Features extensive accounts of fat activist historical roots going back over four decades - Explores controversies and tensions in the movement - Shows that fat activism is an undeniably feminist and queer phenomenon. Fat Activism: A Radical Social Movement is a rare instance of fat people speaking about their lives and politics on their own terms. The book is the result of Charlotte's community-based doctoral research.--Amazon. CA.